Characterization of KPC-Producing Serratia marcescens in an Intensive Care Unit of a Brazilian Tertiary Hospital - Ferreira, Roumayne L.; Rezende, Graziela S.; Damas, Marcelo Silva Folhas; Oliveira-Silva, Mariana; Pitondo-Silva, André; Brito, Márcia C. A.; Leonardecz, Eduardo; Góes, Fabiana R. de; Campanini, Emeline Boni; Malavazi, Iran; da Cunha, Anderson F.; Pranchevicius, Maria-Cristina da Silva (Frontiers in Microbiology, 2020)
Serratia marcescens has emerged as an important opportunistic pathogen responsible for nosocomial and severe infections. Here, we determined phenotypic and molecular characteristics of 54 S. marcescens isolates obtained from patient samples from intensive-care-unit (ICU) and neonatal intensive-care-unit (NIUC) of a Brazilian tertiary hospital. All isolates were resistant to beta-lactam group antibiotics, and 92.6% (50/54) were not susceptible to tigecycline. Furthermore, 96.3% showed intrinsic resistance to polymyxin E (colistin), a last-resort antibiotic for the treatment of infections caused by MDR (multidrug-resistant) Gram-negative bacteria. In contrast, high susceptibility to other antibiotics such as fluoroquinolones (81.5%), and to aminoglycosides (as gentamicin 81.5%, and amikacin 85.2%) was found. Of all isolates, 24.1% were classified as MDR. The presence of resistance and virulence genes were examined by PCR and sequencing. All isolates carried KPC-carbapenemase (blaKPC) and extended spectrum beta-lactamase blaTEM genes, 14.8% carried blaOXA-1, and 16.7% carried blaCTX-M-1group genes, suggesting that bacterial resistance to β-lactam antibiotics found may be associated with these genes. The genes SdeB/HasF and SdeY/HasF that are associated with efflux pump mediated drug extrusion to fluoroquinolones and tigecycline, respectively, were found in 88.9%. The aac(6')-Ib-cr variant gene that can simultaneously induce resistance to aminoglycoside and fluoroquinolone was present in 24.1% of the isolates. Notably, the virulence genes to (i) pore-forming toxin (ShlA); (ii) phospholipase with hemolytic and cytolytic activities (PhlA); (iii) flagellar transcriptional regulator (FlhD); and (iv) positive regulator of prodigiosin and serratamolide production (PigP) were present in 98.2%. The genetic relationship among the isolates determined by ERIC-PCR demonstrated that the vast majority of isolates were grouped in a single cluster with 86.4% genetic similarity. In addition, many isolates showed 100% genetic similarity to each other, suggesting that the S. marcescens that circulate in this ICU are closely related. Our results suggest that the antimicrobial resistance to many drugs currently used to treat ICU and NIUC patients, associated with the high frequency of resistance and virulence genes is a worrisome phenomenon. Our findings emphasize the importance of active surveillance plans for infection control and to prevent dissemination of these strains.